Global Warming and Climate Change - Tiefenbacher, John P. (IntechOpen, 2020)
Global Warming and Climate Change includes scientific and social scientific studies that consider problems stemming from the phenomena of a warming Earth atmosphere, including natural responses to thermal flux, implications for transformations of energy pathways, human actions to adjust, adapt, and mitigate the effects of changing climates, and engineering and design efforts to stop the warming of and reverse the impacts to our environments. A small volume can only touch on several aspects of our challenges and can only offer a small glimpse at the activities of scientists and social scientists around the world, but the array of chapters herein offers unique insight into the scholarship.